Measurement Of Company Performance With Approach Balanced Score Study Case: Regional Drinking Water Company - Kurniati Karim; Dennis Rydarto Tambunan; Nirta Vera Yustanti; Heru Kreshna Reza; Melly Susanti (International Journal of Science, Technology & Management, 2021)
Performance is a process carried out in achieving a result for each company or organization in the stage of providing services or products to customers within a certain period of time in accordance with their duties and functions. This study aims to conduct and see the overall organizational picture of the performance assessment of the Regional Water Company (PDAM) of Sungai Penuh Jambi City using the Balanced Score Card approach. viewed from four perspectives, namely: financial perspective, customer perspective, internal business perspective, and learning and growth perspective. From the results of the research on the Performance Measurement of Regional Drinking Water Companies (PDAM) of Sungai Penuh Jambi City using the Balanced Scorecard approach from a financial perspective through the current ratio, profit margin, operation ratio, return on investment, it shows that the company's financial performance is in good condition despite a decline in sales in 2019 For performance measurement based on customer perspective from customer acquisition, customer retention, customer satisfaction, customer satisfaction can be said to be good, although customer satisfaction that the Regional Drinking Water Company (PDAM) of Sungai Penuh Jambi City in 2020 can be said to be not good. Furthermore, the correlation/correlation of performance based on the perspective of internal business processes on the motivation variable, power alignment, has an influence level of 50.9% with a significance level of <5% or 0%, but for training it has a significance level. below 5% or equal to 0%. The performance based on the learning and growth perspective on employee satisfaction, employee retention, productivity, contributes positively to the company's economic improvement.